1965
DOI: 10.1111/j.1440-1819.1965.tb00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Thrombosis of the Internal Carotid Artery in Children

Abstract: Summary Two cases of internal carotid artery thrombosis in apparently healthy girls were reported. The first case died of massive encephalomalacia and was demonstrated to have widespread occlusion of the circle of Willis and the distal segments of the bilateral internal carotid artery. Since histological changes characterized by numerous thick intimal plaques were similar to those which occur during infectious diseases, it was suspected that chronic tuberculosis or otitis media which were revealed at autopsy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1971
1971
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The changes which have been reported include the marked prominence of surface vessels (Maki and Nakata, 1965;Halonen et al, 1973) and of deep vessels throughout the brain (Vuia et al, 1970), or occlusion of one or more of the components of the circle of Willis (Kawakita et al, 1965). Some authors have described vessels as hypoplastic generally (Vuia et al, 1970) while others described hypoplasia of one or other constituent of the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes which have been reported include the marked prominence of surface vessels (Maki and Nakata, 1965;Halonen et al, 1973) and of deep vessels throughout the brain (Vuia et al, 1970), or occlusion of one or more of the components of the circle of Willis (Kawakita et al, 1965). Some authors have described vessels as hypoplastic generally (Vuia et al, 1970) while others described hypoplasia of one or other constituent of the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have described vessels as hypoplastic generally (Vuia et al, 1970) while others described hypoplasia of one or other constituent of the vessel wall. Nearly all reports include descriptions of an abnormal elastic lamina which was either excessively infolded and thickened (Kawakita et al, 1965;Maki and Nakata, 1965;Vuia et al, 1970), or was intermittent or absent (Harvey and Alvord, 1972;Carlson et al, 1973;Halonen et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Yamashita et al reported autopsy findings of fibromuscular intimal thickenings of a renal artery and fibrocellular intimal thickenings of both coronary arteries in a seven-year-old Japanese girl with Moyamoya disease (12). Kawakita et al mentioned thickenings of the intima by loose connective tissue in the carotid, coronary, renal, hepatic and splenic arteries of a twelve-year-old boy with Moyamoya disease and tuberculosis (9).…”
Section: Clinical Coursementioning
confidence: 99%